PENGARUH MEDIA PEMBELAJARAN WORDWALL TERHADAP MOTIVASI BELAJAR MATEMATIKA PERKALIAN BILANGAN BULAT - Mochammad Agri Triansyah; Ines Sri Suryana (Institut Pendidikan dan Bahasa Invada, 2023)
This research aims to determine the effect of using word wall based educational games in mathematics learning on student learning motivation in grade VI at SDN Bojonggenteng Elementary School. This research is quantitative research using survey methods. The subjects of this research were 87 Class VI students, where the sample was 37 Class VI students. The data collection technique in this research is by using a questionnaire. Information obtained from respondents using this questionnaire was used to determine the effect of using wordwall-based educational games on learning motivation. This research uses partial testing (t test) to determine the hypothesis. The hypothesis results obtained based on the partial test (t test) are 3.552 (tcount) > 2.045 (ttable) with a significance of 0.000 < 0.05. These results show that H₁ is accepted and H₀ is rejected, which means that there is a positive and significant influence between wordwall-based learning media on learning motivation in mathematics learning for class V1 students at SDN Bojonggenteng.